PENGARUH PENERAPAN PENGETAHUAN BISNIS DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA USAHA (Studi Pada UMKM Kota Malang) - Amalia Maulida Nurissalmah; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study is to analyze the effect of business knowledge, to analyze the effect of accounting information systems, and to determine the effect of business performance, knowledge, information systems on business performance in MSMEs in Malang City. The sample in this study used the questionnaire method, namely using several populations to be used as samples. The data of this study were in the form of a questionnaire containing the requirements proposed to SMEs in Malang City. The analytical method of this research is Multiple Linear Regression Analysis, Normality Test, and Classical Assumption Test. The results show that Business Knowledge and Accounting Information Systems simultaneously affect Business Performance. Business Knowledge and Accounting Information Systems partially affect Business Performance.Keywords : Business Knowledge, Accounting Information Systems and Business Performance.